Impact of confined nanofluid jets on the performance of solar Photovoltaic-thermal systems with dust deposition - M. Saif Aldien; Ali Basem; Azher M Abed; Moaz Al-lehaibi; Hussein A.Z. AL-bonsrulah; Ria H. Egami (Results in Engineering)
This study investigates the productivity of a solar panel system subjected to a magnetic field, utilizing cooling tubes and confined jet streams. Combination of PVT (Photovoltaic-thermal) and TEG (Thermoelectric generator) has been utilized. A ferrofluid composed of iron oxide (Fe3O4) nanoparticles dispersed in water was employed to enhance heat transfer within the cooling sections. Key factors analyzed include dust density (ω), jet inlet velocity (Vjet), cooling tube velocity (Vtube), and the Hartmann number (Ha). The results indicate that an increase in dust density (ω) reduces thermal efficiency (ηth) by approximately 8.8 %, underscoring the importance of controlling dust accumulation to maintain optimal performance. In contrast, the application of a magnetic field, quantified by Ha, improves cooling uniformity, leading to a 17.8 % enhancement in thermal efficiency. Higher Ha values specifically contribute to a 1.19 % increase in ηth. Moreover, raising the cooling tube velocity (Vtube) enhances thermal field uniformity by 32 %, further boosting overall system performance. These findings demonstrate the effectiveness of integrating magnetic forces and nanofluids in advancing solar panel technology, offering pathways for more efficient and sustainable energy solutions.